ETIKA PROFESI DALAM PERSPEKTIF MULTIKULTURAL DAN MODERASI BERAGAMA - Nurul Syafawani; Haris Riadi; Alia Nadira (STKIP Pesisir Selatan, 2026)
Objective: Professional ethics are values ​​and norms that serve as guidelines in carrying out tasks professionally and responsibly. In a multicultural society, professional ethics not only demands technical competence, but also the ability to understand and appreciate cultural, ethnic, and religious diversity. This is important because each individual has a different background, so a fair, inclusive, and non-discriminatory professional attitude is needed in providing services. This study aims to examine the application of professional ethics from a multicultural perspective and its relationship with religious moderation. The method used is a qualitative approach through literature studies by analyzing various relevant scientific sources. The results of the study indicate that professional ethics based on multiculturalism emphasizes the values ​​of tolerance, mutual respect, and justice, while religious moderation directs individuals to be balanced, not extreme, and respect differences in beliefs in professional life. Thus, the integration of professional ethics, multicultural values, and religious moderation can create a harmonious and conducive work environment. The application of these values ​​not only improves the quality of service but also strengthens unity in diversity, especially in the context of a pluralistic Indonesian society. Therefore, professional ethics based on multiculturalism and religious moderation are very relevant in facing complex social dynamics.